X linked dominant congenital isolated bilateral ptosis: the definition and characterisation of a new condition. Issue 1 (1st January 2001) - McMullan, T F W; Tyers, A G
Abstract : AIMS: To characterise the inheritance of ptosis in one particular pedigree. METHODS: The pedigree was analysed clinically and genetically to assess the mode of inheritance and to ascribe a gene locus for the condition. RESULTS: Affected members of the pedigree have bilateral symmetrical congenital isolated ptosis, a condition which is linked to genetic markers on the X chromosome in this family. CONCLUSION: A pedigree with dominantly inherited congenital bilateral ptosis is presented. The pedigree exhibits X linked dominant inheritance. A new ophthalmic condition was thereby characterised—namely, X linked dominant congenital isolated bilateral ptosis.